PENGARUH PENGALAMAN KERJA, PENDIDIKAN DAN PELATIHAN TERHADAP PENGEMBANGAN KARIR DI PT. PLN (PERSERO) DISTRIBUSI BALI - Candra, Ni Nyoman Witya; Ardana, I Komang (E-Jurnal Manajemen, 2016)
Career development is a process of improving the ability of individual work achieved in order to achieve the desired career. In order to increase employees' career development, companies need to consider the factors that influence it. The purpose of this study was to determine the effect of work experience, education and training to career development. This research was conducted at PT. PLN (Persero) Distribution Bali. Total sample 64 people using stratified random sampling method. Data collected through observation, interviews and questionnaires. The analysis technique used is multiple linear regression analysis. The analysis finds that work experience positive and significant effect on the career development. Education and training positive and significant impact on career development. To enhance the career development of the company needs to pay attention to the experience of employees so that employees are able to complete the work presented smoothly. The company also must pay attention to and improve the implementation of education and training so that employees have the ability and a better insight about the field they pursue.
Keywords: work experience, education and training, career development